2(p+3)(p+3)+4(p+3)+4=

Simple and best practice solution for 2(p+3)(p+3)+4(p+3)+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(p+3)(p+3)+4(p+3)+4= equation:


Simplifying
2(p + 3)(p + 3) + 4(p + 3) + 4 = 0

Reorder the terms:
2(3 + p)(p + 3) + 4(p + 3) + 4 = 0

Reorder the terms:
2(3 + p)(3 + p) + 4(p + 3) + 4 = 0

Multiply (3 + p) * (3 + p)
2(3(3 + p) + p(3 + p)) + 4(p + 3) + 4 = 0
2((3 * 3 + p * 3) + p(3 + p)) + 4(p + 3) + 4 = 0
2((9 + 3p) + p(3 + p)) + 4(p + 3) + 4 = 0
2(9 + 3p + (3 * p + p * p)) + 4(p + 3) + 4 = 0
2(9 + 3p + (3p + p2)) + 4(p + 3) + 4 = 0

Combine like terms: 3p + 3p = 6p
2(9 + 6p + p2) + 4(p + 3) + 4 = 0
(9 * 2 + 6p * 2 + p2 * 2) + 4(p + 3) + 4 = 0
(18 + 12p + 2p2) + 4(p + 3) + 4 = 0

Reorder the terms:
18 + 12p + 2p2 + 4(3 + p) + 4 = 0
18 + 12p + 2p2 + (3 * 4 + p * 4) + 4 = 0
18 + 12p + 2p2 + (12 + 4p) + 4 = 0

Reorder the terms:
18 + 12 + 4 + 12p + 4p + 2p2 = 0

Combine like terms: 18 + 12 = 30
30 + 4 + 12p + 4p + 2p2 = 0

Combine like terms: 30 + 4 = 34
34 + 12p + 4p + 2p2 = 0

Combine like terms: 12p + 4p = 16p
34 + 16p + 2p2 = 0

Solving
34 + 16p + 2p2 = 0

Solving for variable 'p'.

Factor out the Greatest Common Factor (GCF), '2'.
2(17 + 8p + p2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(17 + 8p + p2)' equal to zero and attempt to solve: Simplifying 17 + 8p + p2 = 0 Solving 17 + 8p + p2 = 0 Begin completing the square. Move the constant term to the right: Add '-17' to each side of the equation. 17 + 8p + -17 + p2 = 0 + -17 Reorder the terms: 17 + -17 + 8p + p2 = 0 + -17 Combine like terms: 17 + -17 = 0 0 + 8p + p2 = 0 + -17 8p + p2 = 0 + -17 Combine like terms: 0 + -17 = -17 8p + p2 = -17 The p term is 8p. Take half its coefficient (4). Square it (16) and add it to both sides. Add '16' to each side of the equation. 8p + 16 + p2 = -17 + 16 Reorder the terms: 16 + 8p + p2 = -17 + 16 Combine like terms: -17 + 16 = -1 16 + 8p + p2 = -1 Factor a perfect square on the left side: (p + 4)(p + 4) = -1 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 7x=29.6 | | 1x=8.4 | | x^2=4x-15 | | 2x^4+6=38 | | x^2+28x-36=0 | | 7p^2-2=0 | | 2t^2+2=0 | | 5k+2=16 | | x=12y+108 | | 6x^2-1734=0 | | y^2-36=0 | | -6+5x=-31 | | -4(3b+9)=24+3(2b-8) | | X^2+7x-36=0 | | x^3+36x=0 | | .8b=1.12 | | 16x-10x= | | 9=y | | x-12y-152=-44 | | 6-4(x+3)= | | 2x^2-10x-6=0 | | 29+-25= | | 37+-42= | | 10x+9=3+2(x-5) | | 6(1+5v)-5(3v-3)=-69 | | 2w^2+17w+36=0 | | x^2+4=68 | | 4y=7x | | 2x-12=10x+20 | | s^2-4s=0 | | 8x+3(2-x)=5x+6 | | 3x^2+7x+3=0 |

Equations solver categories